Pengaruh Brand Awarenes, Brand Acosiation dan Perceived Quality Terhadap Keputusan Pembelian PC Tablet di Kota Padang - Danny Hidayat; Vera Pujani (Management Institute Faculty of Economics Universitas Andalas, 2018)
The objective of this research is to determine the effect of brand awareness, brand association and perceived quality on purchasing decisions for Tablet PCs in Padang City. This research is conducted in Padang and focusing on consumers using a Tablet PC as objects. The population in this research were all consumers who use Tablet PCs in Padang City. Population size is unknown. The sampling technique method was accidental sampling, with a sample of 96 people. The data analysis technique used is the Validity Test and Reliability Test, Multiple Linear Regression Analysis, T test, F test, Coefficient of Determination (R2) assisted by SPSS software. The results of this research indicate that brand awareness, brand association and perceived quality have a significant effect on purchasing decisions for tablet PCs in Padang City partially and simultaneously. Based on the results of the research, 66.9% of the decision to purchase a Tablet PC in Padang City can be explained by brand awareness, brand association and perceived quality, while the remaining 33.1% is explained by other variables not examined in this research.